2015
DOI: 10.1590/1808-2432201505
|View full text |Cite
|
Sign up to set email alerts
|

Nova Lei Dos Portos: Desafios Jurídicos E Perspectivas De Investimentos

Abstract: A situação dos portos brasileiros tem sido identificada como um dos principais entraves para o desenvolvimento econômico do Brasil. Atribui-se esse problema, preponderantemente, aos altos custos e à pouca eficiência nas operações portuárias. Recentemente, com a ediçã da nova Lei dos Portos, foi estabelecido um novo marco regulatório para o setor portuário brasileiro, buscando dar maior agilidade às transações e modernizar o setor. Os arrendamentos portuários passaram a ser regulados de forma semelhante a uma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
2
0
6
Order By: Relevance
“…However, despite the advancement of the Port Modernization Act (8630, of 1993) and the new regulatory framework of the port sector (12.815, of 2013) that have the objective of providing more agility and modernizing the sector, reducing the costs of transactions [4,5], port infrastructure and the quality of services remain issues that affect the agricultural production of the country [14]. According to data by the World Economic Forum pertaining to the Brazilian port infrastructure, compared with the main exporters of corn and soybeans, Brazil was the 122nd position among 144 evaluated countries [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the advancement of the Port Modernization Act (8630, of 1993) and the new regulatory framework of the port sector (12.815, of 2013) that have the objective of providing more agility and modernizing the sector, reducing the costs of transactions [4,5], port infrastructure and the quality of services remain issues that affect the agricultural production of the country [14]. According to data by the World Economic Forum pertaining to the Brazilian port infrastructure, compared with the main exporters of corn and soybeans, Brazil was the 122nd position among 144 evaluated countries [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Reis et al [2] argue that poor logistics of Brazilian infrastructure increases the inland freight of soybean in comparison with the US by 146%. Moreover, Galvão et al [4] [5] showed that Brazilian ports cargo flow grew significantly, around 42% from 2001 to 2011, reaching 886 million (mt) in 2011; this was mainly solid bulk cargo.…”
Section: Introductionmentioning
confidence: 99%
“…Nas últimas décadas, no entanto, ocorreram importantes modificações no setor portuário brasileiro (CRAVEIRO, 2015). Em 1993, foi editada a Lei de Modernização dos Portos, a Lei no 8.630/1993, com atuação sobre o regime jurídico da exploração dos portos organizados e das instalações portuárias e conferindo outras resoluções (FARRANHA et al, 2014).…”
Section: Legislação Do Sistema Portuáriounclassified
“…Com a edição desta nova lei, buscou-se dar maior agilidade às transações e modernizar o setor. Os arrendamentos portuários passaram a ser regulados de forma semelhante a uma concessão de serviço público, destacando-se parâmetros de desempenho e a regulação tarifária (FARRANHA et al, 2014).…”
Section: Nova Lei Dos Portosunclassified
“…Além disso, as novas regras facilitam a instalação de novos terminais portuários privados. Para Farranha et al (2015), um dos objetivos principais da Lei n. 12.815/2013 foi proporcionar mais agilidade e modernizar o setor, reduzindo os custos das transações.…”
Section: Introductionunclassified